Diagnostic male secondary sexual structures and wing patterns in the Thereus genena species group (Lepidoptera: Lycaenidae: Theclinae) with the description of nine new species from Colombia, Peru, Brazil and French Guiana - Faynel, Christophe; Huertas, Blanca; Crom, Jean François Le; O'brien, Richard; Fåhraeus, Christer (Zootaxa, 2025)
A review of the genena species group of Thereus Hübner is provided, based on literature, barcoded specimens, genome type material and recent collecting data, as part of an ongoing revisionary work on this genus. Previously, the genena species group contained five species and four synonyms, this study reveals nine new species and two previously unrecognized species whose names are here removed from synonymy. Thereus geminus Faynel & Fåhraeus sp. nov. (type-locality: Peru) is similar to T. endera but the ventral hindwing postmedian line is straight (no gap as in T. endera). Thereus cacao Faynel & Fåhraeus sp. nov. (type-locality: French Guiana) is close to T. endera but males have blue-violet coloration dorsally (compared to the grey-dull blue of T. endera) and the ventral postmedian line is displaced on the forewing. Thereus antecum Faynel & Fåhraeus sp. nov. (type-locality: French Guiana) is a large species reminiscent of Thereus endera (Hewitson), with a different shape of the postmedian line ventrally. Thereus chontachaca Faynel, Fåhraeus & González-Mercado sp. nov. (type-locality: Peru) is similar to Thereus ortalus (Godman & Salvin) and Thereus praxis (Godman & Salvin), although smaller and with a bigger black scent patch on the male dorsal forewing. Thereus ramirezi Faynel, Huertas & Fåhraeus sp. nov. (type-locality: Peru) is characterized by a wave-shaped dorsal edge of the vinculum supporting brush organs in the male genitalia, a character that is unique in the genena species group. Thereus borbaensis Faynel, O’Brien & Fåhraeus sp. nov. (type-locality: Brazil) is bigger than the previous two species with a wider black scent patch on the male forewing. Thereus confusus Faynel & Fåhraeus sp. nov. (type-locality: Brazil) was previously confused with T. ortalus but differs by its flattened oval scent patch on the male dorsal forewing. Thereus praxioides Faynel & Fåhraeus sp. nov. (type-locality: French Guiana) resembles T. praxis but differs by having thinner black margins and different oval scent patch on the male forewing. Thereus aguacatal Faynel, Le Crom, & Fåhraeus sp. nov. (type-locality: Colombia) looks like T. ortalus but has a single androconial patch on the male dorsal forewing. In addition to these new descriptions, some species-names are removed from synonymy: Thereus angulus (Le Crom & K. Johnson), stat. rev., type locality: Colombia (Meta), from T. endera, type-locality: Brazil (Amazonas) and Thereus ortaloides (Lathy), stat. rev., type-locality: Brazil (Rio de Janeiro), from T. ortalus, type-locality: Mexico (Veracruz). Consequently, we reinstate these nominal taxa to their original status, arrangements that are supported also by genomic work and barcoding of type material. To stabilize nomenclature, lectotypes are designated for Thecla endera Hewitson, Thecla genena Hewitson, Thecla praxis Godman & Salvin and Thecla ortalus Godman & Salvin. A neotype is designated for Thecla tiasa Hewitson to define this nominal taxon objectively. A key to identify species of the genena species group is provided using male characters.